Autopsy of a patient with restrictive cardiomyopathy with and MYH7 mutation - Hiroaki Kawano; Koichi Kawamura; Munetake Kanda; Nozomi Ueki; Muneo Tanigawa; Mitsuaki Ishijima; Yuji Matsumoto; Masahiro Nakashima; Koji Maemura (Elsevier, 2021)
Restrictive cardiomyopathy (RCM) is a rare type of primary myocardial disease, and its pathological features remain unclear. We report the case of a 78-year-old Japanese woman with RCM and MHY7 mutation who died of heart failure 13 years after the diagnosis. Upon autopsy, focal myocyte amorphous degeneration positive for ubiquitin was revealed, as well as myocardial disarrangement and interstitial fibrosis. Electron microscope demonstrated electron-dense structure in the cardiac myocytes. These may be one of the pathological features of RCM.